2015
DOI: 10.1590/0037-8682-0121-2013
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS epidemic in the State of Amazonas: characteristics and trends from 2001 to 2012

Abstract: 70www.scielo.br/rsbmt I www.rsbmt.org.br Revista da Sociedade Brasileira de Medicina Tropical 48(Suppl I):70-78, 2015http://dx.doi. org/10.1590/0037-8682-0121-2013 Review Article ABSTRACT A scoping review was conducted to describe the epidemiological characteristics of the human immunodefi ciency virus/acquired immunodefi ciency syndrome (HIV/AIDS) epidemic in the State of Amazonas, Brazil, from 2001 to 2012, and temporary patterns were estimated from surveillance data. The results suggest that in its third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 17 publications
(23 reference statements)
4
18
0
1
Order By: Relevance
“…16 Em relação ao comportamento sexual na pesquisa realizada no Amazonas, verificou-se uma tendência significativa no aumento de casos tanto em indivíduos homossexuais quanto em heterossexuais. 17 Esses dados corroboram com os resultados encontrados em nosso estudo.…”
Section: Discussionunclassified
“…16 Em relação ao comportamento sexual na pesquisa realizada no Amazonas, verificou-se uma tendência significativa no aumento de casos tanto em indivíduos homossexuais quanto em heterossexuais. 17 Esses dados corroboram com os resultados encontrados em nosso estudo.…”
Section: Discussionunclassified
“…Trends and challenges of HIV/AIDS in the State of Amazonas are analyzed by Oliveira et al (15) to reveal a worrying scenario characterized by the epidemic in regions where the socio-economic conditions, the quality and quantity of health services, as well as access to services are real obstacles to the full implementation of control program actions. Attention should focus on a possible imminent emergence of syndromes associated with co-infections with pathogens prevalent in the Amazon scenario.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Attention should focus on a possible imminent emergence of syndromes associated with co-infections with pathogens prevalent in the Amazon scenario. HIV/AIDS is currently the fastest growing disease in the North of Brazil, with similar endemic features to the 1980s including late diagnosis and high frequency of opportunistic infections because of non-adherence to antiretroviral therapy (15) .…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…As of 2018, more than 900,000 AIDS cases had been reported in Brazil and approximately 600,000 are on ART 1 . After a signi cant reversal in mortality due to the adoption of ART in 1996, deaths related to the HIV/AIDS epidemic have been showing a downward trend in Brazil as a whole, however this trend is still subtle in the northern and northeastern regions 1,3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The Fundação de Medicina Tropical Doutor Heitor Vieira Dourado (FMT-HVD), located in the middle of the city, is a tertiary care hospital which performs HAART services and admits moderate to severely ill people living with HIV. This represents a contingent greater than 85% of all patients receiving ART, as well as concentrating data on incidence levels of AIDS, mortality rates and late diagnosis 2,5 . Studies on the HIV/AIDS epidemic in the region have indicated over time that the trend in the number of cases continues to increase principally in men, that tuberculosis (TB) is still the leading cause of death, and that respiratory failure is the main cause of hospital admission for these patients [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%